2017
DOI: 10.1107/s2053229617003084
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state NMR meets electron diffraction: determination of crystalline polymorphs of small organic microcrystalline samples

Abstract: A combination of solid-state NMR (ssNMR) and electron diffraction (ED) has been used to determine the crystalline polymorphs in small-organic microcrystalline molecules. Although C cross-polarization magic angle spinning (CPMAS) is a widely used method for determining crystalline polymorphs, even in a mixture, it sometimes fails if the molecular conformations are similar. On the other hand, ED can, in principle, differentiate crystalline forms with different lattice parameters, even when they have very similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…SSNMR partially addresses these questions via the 1 H, 14 N, and 15 N signals, which can be easily observed, especially under very fast MAS conditions 29 . Both 1 H– 14 N and 1 H– 15 N 2D SSNMR spectra contained two covalently bonded N–H signals from the α-amino group and imidazole ring (see Supplementary Figure 2), which clearly indicated that only one of the two nitrogen atoms of the imidazole ring was protonated 30 . The peak at − 280 ppm in the 14 N dimension empirically suggested the presence of NH 3 + , as small quadrupolar couplings with high symmetry in 14 NH 3 + give rise to a small second-order quadrupolar shift of 14 N 30 .…”
Section: Resultsmentioning
confidence: 99%
“…SSNMR partially addresses these questions via the 1 H, 14 N, and 15 N signals, which can be easily observed, especially under very fast MAS conditions 29 . Both 1 H– 14 N and 1 H– 15 N 2D SSNMR spectra contained two covalently bonded N–H signals from the α-amino group and imidazole ring (see Supplementary Figure 2), which clearly indicated that only one of the two nitrogen atoms of the imidazole ring was protonated 30 . The peak at − 280 ppm in the 14 N dimension empirically suggested the presence of NH 3 + , as small quadrupolar couplings with high symmetry in 14 NH 3 + give rise to a small second-order quadrupolar shift of 14 N 30 .…”
Section: Resultsmentioning
confidence: 99%
“…14 H/ 1 H HMQC experiments were also used in this case to establish N protonation state, with the advantage that experiments with longer mixing times (600 μs) often (although not always) also showed correlation peaks corresponding to H…N in a N-H…N bonding arrangement, hence providing valuable insight into intermolecular hydrogen bonding. Different protonation states of imidazole rings have also been clearly observed in 1 H, 14 N HMQC spectra [79], which were acquired in less than an hour using 90 kHz MAS at 14.1 T. N,H proximity has also been investigated by 1 H NMR, e.g. 1 H spectra acquired at 90 kHz MAS with and without 14 N decoupling clearly H atoms bonded to nitrogen [80].…”
Section: Via 15 N (And 14 N) Nmrmentioning
confidence: 94%
“…For example, the 13 C NMR spectra of the α and γ polymorphs of glycine are very similar, but their 1 H NMR spectra (acquired using homonuclear decoupling) are quite distinct [78]. Similarly, the differences in 13 C shifts between A and B polymorphs of histidine hydrochloride are less than 1 ppm [79]. Subtle differences were visible in 1 H spectrum, but the forms were most cleanly differentiated by 1 H DQ/SQ spectra, with the differences rationalised in terms of intermolecular contacts.…”
Section: Information From Chemical Shiftsmentioning
confidence: 99%
“…Solid state NMR along with electron diffraction (ED) appear to be promising tools with emerging potential in these cases. In a recent study, Oikawa et al [39] demonstrated the combined use of multidimensional ssNMR and ED to discriminate (in finger print patterns) three crystalline polymorphs of L-histidine namely orthorhombic (form A) and monoclinic (form B) samples of L-histidine (shown in Figure 7), and L-histidine •HCl•H 2 O. Since intense electron beam induces degradation in organic molecules, very mild level of irradiation was used, to avoid such degradation effects.…”
Section: Solid State Nmr and Electron Diffraction Techniquesmentioning
confidence: 92%